ANALISIS PIUTANG TIDAK TERTAGIH DAN UTANG TIDAK TERBAYAR TERHADAP ARUS KAS OPERASIONAL PADA CV CIPTA KARYA HARMONY - Cisa Dena Putri; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
Operational cash flow is a factor of the company's survival, so that positive cash flow is needed to support the company's activities. Factors that can affect operational cash flow are receipts from accounts receivable and debt payments. The purpose of this study is to analyze uncollectible receivables and unpaid debts to operational cash flow on CV Cipta Karya Harmony. This research method uses descriptive qualitative analysis which analyzes data by describing or describing data that has been collected and the results of this study indicate that uncollectible receivables and unpaid debt affect the company's operating cash flow.